DNA methylation in paediatric germ cell tumours - Mohamed Noor, Dzul Azri (2013)
Germ cell tumours (GeTs)affect both paediatric and adult populations, and can occur either in gonadal or extragonadal regions along the body's ventral midline. These tumours can be broadly categorized into two subgroups, seminomatous (SEM) or nonseminomatous (N-SEM). The latter can be further subcategorized into embryonal carcinoma (EC), teratoma, yolk sac tumour (YST) and choriocarcinoma (eC) according to their differentiation. As in many other tumours, DNA methylation has been proposed to be involved in GCTdevelopment. However to date, most studies were performed using adult testicular GCTs. Furthermore, these studies only include a handful of genes in their analysis. Thus, the roles of DNA methylation in paediatric and extragonadal GeTs have not been explored. Therefore, this project attempted to fill this gap in knowledge by performing methylation analysis in a cohort of paediatric GCT samples and GCTcell lines. Although paediatric GCTsmostly consist of teratomas, seminomas or YSTs, only the latter two were included in the methylation analysis as they were the only samples in the available tumour bank. Using the methylation level of L1NE-l repeat elements as a measurement of global genome methylation, we found that both paediatric seminoma and YST samples displayed global hypomethylation as compared to somatic controls. However, when methylation at gene promoter regions was investigated using Illumina Golden Gate methylation arrays, seminoma and YST exhibited very different methylation features. YSTs were found to be highly methylated at many of the sites investigated. Surprlslnglv, we found that the methylation features in seminoma were similar to the somatic controls. From this analysis, we identified 85 genes that were differentially methylated in the VSTs. However, by correlating our methylation data with the expression array data performed by our collaborators on the same samples, only eight of these genes (PYCARO, CASPB, C02, HOAC9, TFAP2C, ETV1, EV/2A, HLA-F) were differentially expressed. As in previous GCTstudies, our analysis was focused on the methylation at epG islands. During the course of this project technological advancement led to the creation of new methylation arrays that offer wider genome coverage. One example is the Infinium Methylation 450K array that covers more than 450,000 CpG sites and includes regions flanking the CpG islands such as the CpG shores and CpG shelves. Since no previous GCT studies have attempted to investigate methylation in those regions, we utilized this methylation array on four GCTcell lines; TCAM2 (seminoma), NT2Dl (teratocarcinoma), GCT27 (embryonal carcinoma) and GCT44 (yolk sactumour). Similar to previous GCT studies, we found that nonseminomatous GCT cell lines displayed higher methylation at the CpG islands as compared to the seminoma cell lines. Strikingly, expanding our analysis to other regions (CpG shores and shelves etc.) revealed that each GCT subtype exhibited distinct methylation features. Both ECand teratoma cell lines displayed higher methylation than the seminoma and YST cell lines at all regions. Interestingly, the YST cell line only showed higher methylation than the seminoma cell line at the CpG islands and to a lesser extent at the CpG shores while the seminoma cell line exhibited higher methylation at the CpG shelves as compared to the YST cell line. This is the first time such features have been reported for GCTs. From this Infinium methylation data, we have also identified a high number of hypermethylated genes including those that are uniquely methylated for each cell line. By correlating this methylation data with Affymetrix gene expression data, 98 genes that were differentially methylated and differentially expressed in the YST cell line have been identified. However, further analysis needs to be performed to understand the role of these genes in YST development. As in other types of tumour, the hypermethylation observed in the YST cell line might be caused by many epigenetic modifiers. Using real-time RT-PCR on three epigenetic modifiers (DNMT38, EZH2, SUZ12), we found that DNMT38 was highly expressed in the YST samples and cell line as compared to the seminoma samples and cell line. This suggests that DNMT38 might contribute to YST hypermethylation and resulting differences in their biology. However, knockdown of DNA methyltransferases (DNMTs) and DNMT38 using 5-azadeoxycytidine and microRNA-29b respectively, did not seem to have any effect on the response of all four GCT cell lines towards cisplatin. On the other hand, both knockdowns only caused little effect on cell migration; affecting only the seminoma and YST cell lines. Nonetheless, further analysis is still needed to fully assess the role of DNA methylation in regulating cell behaviour. In summary, paediatric YSTs displayed hypermethylation at many promoter regions as compared to seminomas. Meanwhile, methylation analysis at regions outside of CpG islands in GCTcell lines revealed unique methylation features for each GCT subtype which might indicate different underlying mechanisms in their development. Further analysis on genes found to be differentially methylated and differentially expressed in both paediatric and GCTcell lines are now needed to fully establish their role in GCT development.